2021
DOI: 10.12944/crnfsj.9.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of CHAGURO Made of Chayote (Sechium edule) and Tuna (Thunnus sp.) on Rats Induced with Streptozotocin-Nicotinamide and a High-Fat Diet

Abstract: This study was conducted to develop Chaguro, a low-cost supplementary food made of chayote (Sechium edule (Jacq.) Swartz) and tuna fish (Thunnus sp.), for diabetes and dyslipidemia diet therapy. In order to find a formula with effective hypoglycaemic and antidyslipidemic properties, dried tuna and chayote were mixed at different ratios: F1 (75% tuna, 25% chayote), F2 (50% tuna, 50% chayote), and F3 (25% tuna, 75% chayote). Thirty male Sprague Dawley rats were assigned into healthy control group or groups induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This study is also follow-up from a previous study in experimental mice. 10 In particular, the 60-day intervention of functional food CHAGURO could lower the chol/HDL ratio in our subjects. However, an in-depth exploration of the variables related to obesity is required, in order to understand the complex schemes or mechanisms of siamese pumpkin and tuna-based powder (CHAGURO) as a functional food which is both antiobesity and antidiabetic.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…This study is also follow-up from a previous study in experimental mice. 10 In particular, the 60-day intervention of functional food CHAGURO could lower the chol/HDL ratio in our subjects. However, an in-depth exploration of the variables related to obesity is required, in order to understand the complex schemes or mechanisms of siamese pumpkin and tuna-based powder (CHAGURO) as a functional food which is both antiobesity and antidiabetic.…”
Section: Resultsmentioning
confidence: 61%
“…The formulation used is the formulation selected (best) based on the analysis of macronutrients, micronutrients, and organoleptic substances that have been published in the journal of the Ministry of Health of the Republic of Indonesia. [9][10][11] Here are the formulations:…”
Section: Siamese Pumpkin and Tuna-based Powder (Chaguro) Product Preparationmentioning
confidence: 99%
“…In the elaboration of chaguro , different proportions of tuna fish and S. edule were tested. Results revealed that the combination of 75% of dry tuna fish mixed with 25% of S. edule is useful to induce lower blood glucose and improve the lipid profile in DM and dyslipidemia [ 137 ].…”
Section: Selected Species Of the Cucurbitaceae Family Used In Mexico ...mentioning
confidence: 99%
“…The formulation used is the formulation selected (best) based on the analysis of macronutrients, micronutrients, and organoleptic substances that have been published in the journal of the Ministry of Health of the Republic of Indonesia. [9][10][11] Here are the formulations: REVISED Amendments from Version 1 1. Title: we have rewritten the title by deleting "HbA1c, HDL-C".…”
Section: Siamese Pumpkin and Tuna-based Powder (Chaguro) Product Prep...mentioning
confidence: 99%